Design of Digital Based Volley Ball Basic Techniques Test Instrument - Asep Suharta; Amir Supriadi; Nurkadri Nurkadri (Budapest International Research and Critics University, 2021)
This study aims to design a digital-based volleyball basic technical skill test instrument using internet technology as its application. This study uses a research and development design method (Research and Development) used in this study is the Borg and Gall development model with 7 steps of potential problems, data collection, product design, product validation, design revision, product trial, product revision, trial usage, product revision, and production. This learning product was developed in the design of a digital-based volleyball basic technique test instrument. The products of this research are 1) produce a basic volleyball technical test instrument application product used in smartphones, 2) produce a villi ball basic technical instrument product that is easily accessible via the internet